Faktor-Faktor Yang Mempengaruhi Tingkat Pengangguran Terbuka Di Eks Karesidenan Pati Periode 2017-2020 - Alma Ikhtiar Zusen (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2022)
Abstract Unemployment is an employment problem that is often faced by every country, especially developing countries such as Indonesia. This study aims to analyze and find out how much influence the human development index, job opportunities, and the number of poor people have on the open unemployment rate in the former Pati Residency in 2017-2020. The sample of this research was conducted in 6 regencies/cities in the former Pati Residency. This type of research is quantitative research, and uses secondary data obtained from the Central Statistics Agency (BPS). The data analysis method used is panel data regression which combines time series data and cross section data. The best model in this study is the Fixed Effect Model (FEM). Based on the results of data analysis shows that all variables, namely the human development index, job opportunities, and the number of poor people have a significant effect on the open unemployment rate.